PENGARUH SELF-CONCEPT TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Subawo, Made; Sirad, La Ode; Asizah, Desi Nur (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
This study aims to determine the effect of self-concept on the mathematical creative thinking ability of class VIII SMPN 1 Loea. This type of research is Ex-Post Fact with a quantitative approach. The sample in this study consisted of 30 students of class VIII SMPN 1 Loea. The research instrument used is a self-concept questionnaire consisting of 23 statements and a mathematical creative thinking ability test consisting of 5 questions. The results showed that : 1) there is 1 student with high category self-concept, 11 students with moderat category and 3 students with low category and 3 students with low category ; 2) there are 3 students with creative thinking skills which are classified as very creative, 4 students in the creative category, 15 students in the quite creative category, 6 students in the less creative category and 2 students in the non-creative category; and 3) there is a significant positive effect of self-concept on the mathematical creative thinking ability of class VIII SMP Negeri 1 Loea with the percentage contribution of the influence of the self-concept variable on the mathematical creative thinking ability of 53.8%